WalliD: secure your ID in an Ethereum Wallet - Tavares, M.; Veiga, F.; Guerreiro, A.; Campos, A.; Coutinho, C. (Proceedings of the 9th IEEE-TEMS international Conference on Intelligent Systems (IS 2018), 2018)
Businesses and organizations have for long been trying to tackle the most prominent issues regarding identity management and systems. Traditionally, the proof of trust concerning the identification of a citizen, a customer or a participant in any business or transaction consisted always in a physical evidence (e.g., a signature, fingerprint, photo or other) whose value would rely on a trusted third-party such as a notary or attorney that confirmed the veracity of that physical evidence. More recent approaches include novel types of evidence such as digital certificates, but still these have no value unless they are issued and signed by a trusted centralized third-party that confirms the authenticity of the certificate. These are then often used by businesses to identify and trace their parties and stakeholders, in a process known as “Know Your Customer” (KYC). This process is often slow and requires costly human intervention. This paper presents WalliD, a decentralized approach of a secure protocol to handle customer identification using Blockchain. The paper then shows a proof of concept workflow implementation of this protocol developed using an Ethereum Wallet.